Value-added tax and economic efficiency: role of country governance - Chan, Sok Gee; Ramly, Zulkufly; Mustapha, Mohd Zulkhairi (panaeconomicus, 2018)
This paper examines the impact of VAT on economic efficiency, which while regarded as distortionary remains inevitable for economic development. Using data from 115 countries from 1984 to 2014, this research further investigates the moderating role of country governance on the link between VAT and economic efficiency. The results suggest that the extent to which country governance mitigates the effect of VAT on economic efficiency is contingent upon the way the country groups prioritize the development of each institutional factor. We find that high corporate tax countries benefit more from higher quality country governance. These findings confirm the role of country governance in better enforcement of tax policy to create less detrimental effects for economic growth. Therefore, better country governance makes taxation more affordable in high corporate tax countries.